The Relationship between the Neighborhood Safety and Nutritional Status of Children in Baghdad City, Iraq - Hasanain Faisal Ghazi; Zaleha Md. Isa; Shamsul Azhar Shah; Mohammed A. Abdal Qader; Tiba Nezar Hasan; AL-abed Ali AL-abed (Journal of Nutrition and Metabolism)
Introduction. The neighborhoods where the children live play an important role in their development physically and mentally. The objective of this study was to assess the relationship between neighborhood safety and child nutritional status in Baghdad city, Iraq. Methods. A cross-sectional study was carried out in Baghdad city, Iraq, among 400 primary school children from 4 schools. BMI-for-age Z score was used to assess the nutritional status of the children. Newly developed questionnaires on neighborhood safety were distributed to the parents to answer them. Results. In this study, males were more predominant than females with 215 participants compared to 185 females. A total of 49% were normal weight, 38.8% either overweight or obese, and only 12.2% underweight. There was a significant relationship between father education, father and mother working status, family income, and children nutritional status (P=0.10, 0.009, <0.001, 0.37), respectively. The association between neighborhood safety variables and child nutritional status was significant except for worrying about child safety and thinking of leaving the neighborhood (P=0.082, 0.084), respectively. Conclusion. Nutritional status of school children continues to be a public health issue in Iraq especially Baghdad city. There was a significant association between neighborhood safety and children nutritional status.